Coral: A Framework based on Social Network Analysis to Support the Startup Ecosystem Management - Escalfoni, Rafael; Oliveira, Jonice (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Startup ecosystems are business communities continually unfolding where different actors interact in symbiotic activities to create mutual benefits. A smart startup ecosystem demands an understanding of the interests, capabilities, and affinities among members to take harmony and ensure the group's prosperity. The absence of such mechanisms would compromise the innovation process efficiency, and the environmental imbalance might lead to behaviors harmful to each participant's community to identify convergences and possible partnerships that can help in the development of new business. From this problem, our main contribution is the Coral framework - a social network analysis approach to assist in evaluating relationships in communities. Based on a set of two observational studies in industrial cases, we verified that it is possible to describe the social and material aspects needed to enhance integration and provide greater network efficiency.